2014
DOI: 10.1364/oe.22.0a1303
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of electroluminescence enhancement on green LEDs mediated by surface plasmons

Abstract: We experimentally demonstrate the 1.5-fold enhancement of the electroluminescence (EL) of surface-plasmon (SP)-mediated green LEDs. On the p-clad surface of InGaN/GaN multi-quantum well LEDs, a 2-dimensional, second-order grating structure is textured and coated with an Ag electrode. With this setup, a larger EL enhancement factor is obtained at a higher injected current, which suggests that SP-LEDs can be a possible solution to efficiency droop, which is one of the main problems in developing high-power LEDs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These results demonstrated that the improve the light extraction efficiency and SPP of GaN-LED. [51][52][53][54] If the appropriate micro-/nanogratings are fabricated on the designed or optimized structure in this article, the emission efficiency will be further enhanced. In recent years, a large number of new technologies about LED have emerged.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…These results demonstrated that the improve the light extraction efficiency and SPP of GaN-LED. [51][52][53][54] If the appropriate micro-/nanogratings are fabricated on the designed or optimized structure in this article, the emission efficiency will be further enhanced. In recent years, a large number of new technologies about LED have emerged.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…First of all, there are several technical difficulties in realizing 10e20 nm thin p-GaN layer without any serious damage of the system. When one control the separation gap by etching methods, for example, the active layer could be easily damaged [19], and the overall improvement factor reported in a recent experiment is around 1.5-fold with the separation gap of 30 nm [20]. It must be challenging to technically get the separation gap below 20 nm and to estimate an attainable improvement in such situations by further controlling the radiation direction.…”
Section: Directional Emission and The Light Extraction Efficiencymentioning
confidence: 99%
“…However, it is not straightforward to experimentally control the separation gap on demand. When the metal grating is patterned directly on the p-clad layer by dry etching methods, the damage in the p-clad and the active layers becomes more severe with a smaller separation gap [16]. In this study, we adapted a different approaching of forming a grating on an additional layer of the p-clad and over-coating it with Ag.…”
Section: Introductionmentioning
confidence: 99%